The Würmian Late-Glacial and early-Holocene vegetation and environment of Gourds des Aillères in the Monts du Forez (Massif Central, France) based on pollen and macrofossil evidence. (30th October 2022) - Bos, Johanna A.A.; Birks, Hilary H.; van der Knaap, Willem O.; van Leeuwen, Jacqueline F.N.; Janssen, C.R.
Abstract: Although there is a long history of palaeoecological investigation in the Massif Central, detailed reconstruction of the flora, vegetation, and environment in the Late Pleniglacial, the Würmian (Weichselian) Late-Glacial, and early Holocene in the Monts du Forez (Massif Central, France) is still largely lacking. We inferred the palaeoecology of the area from pollen, spores, and plant macrofossils preserved in the sediments of the palaeolake Gourds des Aillères (1335 m a.s.l.). The lake formed in a glacial depression left by retreating glaciers at the start of the Bølling period, ca. 14700 cal yr BP. Sediment chronology is based on radiocarbon dating and correlation with other, radiocarbon-dated palynological records from the Monts du Forez. Changes in the regional and local vegetation during the Late-Glacial and early Holocene could be correlated to the major climatic events identified in the Greenland oxygen isotope records. We made a highly detailed reconstruction of the changes in the floral diversity and vegetation in and around the lake. After the steppe-tundra of the Late Pleniglacial, local vegetation cover increased and developed into shrub tundra with a few trees forming the tree line in the Bølling and Allerød, with a short reversion during the Older Dryas. During the Younger Dryas trees were eliminated around the site and vegetation was reduced in diversity and density. In the early Holocene, birch ( Betula ) woodland with some pine ( Pinus ) developed and was then replaced by mixed oak woodlands with Corylus. The forest limit rose above the lake. Changes in the lake ecosystem, lake-levels, and nutrient availability were also reconstructed. Hydroseral overgrowth of the lake to a Sphagnum peatbog took >6000 years.